Perencanaan Bumi Perkemahan Alun-Alun Suryakencana Taman Nasional Gunung Gede Pangrango, Jawa Barat - Muttaqin, Imam; Semarajaya, Cokorda Gede Alit; Yusiana, Lury Sevita (Jurnal Arsitektur Lansekap; Vol.4, No.1, April 2018DO - 10.24843/JAL.2018.v04.i01.p04, 2018)
Camping ground planning of Alun-alun Suryakencana in Mt. Gede Pangrango National Park, West Java. A good campsite requires a plan. Planning is done zoning area that can be used as a camping area without disturbing the existing ecosystem and equipped facilities so that users can feel comfortable while in the area of the campground. Alun-alun Suryakencana at an altitude of 2750 m asl is part of the Mount Gede Pangrango National Park of West Java. This research was conducted in October 2016-August 2017, this research method refers to Rachman's (1984) complete thinking process in Norma (2013) which applies secondary data analysis at field study stage which consists of inventory, analysis, synthesis, concept, and planning. The final result of this planning is a Campsite Plan that is implemented in Alun-alun Suryakencana.